Quality Characteristics of Guava (Psidiumguajava L. Ev. Kampuchea) in Response to Hydrocooling Time, Storage Temperature and Storage Duration - James Silip, Jupikely (2003)
The effects of cooling time, storage temperature and storage duration on the guava cv. Kampuchea were determined. Freshly harvested mature-green guava were precooled at 1/8, 1/4 and 112 cooling time using a modified hydrocooler and stored at 5, 10 and 15°C for 1,2,3,4,5 and 6 weeks. Sample zero cooling time (control treatment) was only washed with distilled water (26.0±1.0°C) for about one minute before storage. Only fruits which are well-formed, uniformed-size (350±50 g) and free from blemishes were selected for the experiment. The experimental design carried out RCBD with a factorial arrangement of treatments (4 cooling times x 3 storage temperatures x 6 duration of storage) with three replications, and two fruits for each replication. The results indicated that cooling time only effected the browning but it did not significantly effect the visual appearance, skin colour, weight loss, soluble solids concentration, titratable acidity, pH level and vitamin C. Precooled fruit at 118 had a lower incidence of browning compared to non-precooled and precooled at 114 and 1 12. Significant cooling time x storage temperature interaction only affected water loss. Weight loss was lower when fruits were precooled compared to when they are non-precooled and stored at 15 0c. Treatment combination of storage temperature x storage duration were found to have significant effects on the visual appearance, skin colour, weight loss and soluble solids concentration. However, the treatment did not significantly effect browning, titratable acidity, pH level and vitamin C. Storage temperature of 10 °C showed beneficial effect in the decrease of the loss of visual appearance, delayed changes on the skin colour, gave the lowest weight loss, and the lowest changes of soluble solids concentration. Acceptable visual appearance of the fruit stored at 10°C was up to 3.6 weeks compared to only 1.6 and 1.3 weeks for the fruit stored at 5 and 15°C, respectively. The limit of acceptable L*, C* and hO changes in this study were 65.33±3.3, 43.0±0.5 and I 13 . 83±2.5, respectively and this colour space values corresponded to pale green fruit. The permissible water loss of 6% which equilibrium to the limit of acceptable visual appearance in fruit stored at 10°C was prolonged to 3.5 weeks compared to only 1.4 and 0.8 weeks in the fruit stored at 5 and 15°C, respectively. Maximum accumulation of soluble solids concentration in fruit stored at 10°C was found lowest at only 5.43% compared to 6.43% on both fruit stored at 5 and 15°C. In addition, respective to the temperature treatments the fruit stored at 10°C was found to have the lowest incident on browning compared to those stored at 5°C while the fruit stored at 15°C were ripening, developing senescence, shrivelling and freckles. Results of this research can be used by guava producers in deciding the time level for their precooling and temperature setting for their cold room.